Chronotypology: A Comparative Method for Analyzing Game Time. Issue 7 (13th May 2019) - Jayemanne, Darshana
This article presents a methodology called "chronotypology" which aims to facilitate literary studies approaches to video games by conceptualizing game temporality. The method develops a comparative approach to how video games structure temporal experience, yielding an efficient set of terms—"diachrony, " "synchrony, " and "unstable signifier"—through which to analyze gaming's "heterochronia" or temporal complexity. This method also yields an approach to the contentious topic of video game narrative which may particularly recommend it to literary scholars with an interest in the form. Along with some examples from conventional games, a close reading of the "reality-inspired" game Bury Me, My Love will serve to demonstrate the use of a chronotypological approach.